2020
DOI: 10.1007/s10815-019-01684-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with subchorionic hematoma formation in pregnancies achieved via assisted reproductive technologies

Abstract: Purpose To determine if certain clinical and/or embryologic factors are independently associated with the increased prevalence of subchorionic hematoma (SCH) among pregnancies achieved via in vitro fertilization (IVF) with fresh embryo transfer (ET). Design Retrospective chart review. Methods In this retrospective study, data were abstracted from 210 autologous oocyte IVF clinical pregnancies that resulted from fresh ET at a single fertility center from January 2012 through December 2016. Clinical and embryolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…While a prior meta‐analysis demonstrated increased risk of miscarriage in the fertile population with SCH, 5 a 2019 study demonstrated no increased risk 1 . Similarly, in other studies examining only the infertile population, there was no association between SCH and first trimester pregnancy loss 3,13,18 . Notably, these studies did not assess for the presence of symptoms and whether they impacted risk of miscarriage.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…While a prior meta‐analysis demonstrated increased risk of miscarriage in the fertile population with SCH, 5 a 2019 study demonstrated no increased risk 1 . Similarly, in other studies examining only the infertile population, there was no association between SCH and first trimester pregnancy loss 3,13,18 . Notably, these studies did not assess for the presence of symptoms and whether they impacted risk of miscarriage.…”
Section: Discussionmentioning
confidence: 95%
“… 1 Similarly, in other studies examining only the infertile population, there was no association between SCH and first trimester pregnancy loss. 3 , 13 , 18 Notably, these studies did not assess for the presence of symptoms and whether they impacted risk of miscarriage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the incidence of SCH in pregnant women with assisted reproduction is higher than that in women with natural pregnancy, and frozen embryo transfer and blastocyst transfer increase the risk of SCH ( 17 ). A previous study demonstrated that the transfer of poor blastocyst trophoblast cells can notably increase the risk of SCH, which may be related to the long-term in vitro culture of blastocysts and abnormal placental development ( 18 ). So et al ( 19 ) assumed that uterine cavity surgeries, such as endometrial polyp removal and hysteroscopy prior to embryo transfer, would damage the endometrium and affect the normal development of the placenta.…”
Section: Etiology Of Schmentioning
confidence: 99%
“…Subchorionic hemorrhage, blood clot or collection of blood between the uterine lining and the gestational sac, is a relatively common condition during early pregnancy and can cause varying degrees of concern for expectant mothers. 2 It may result from the separation of the chorion. 3 Majority of cases resolve spontaneously without causing harm to the pregnancy.…”
Section: Introductionmentioning
confidence: 99%